Investment-Led Growth? A Panel Data Analysis of Investment, Trade Openness, Inflation, and Private Credit in Five Developing Countries, 2010–2024 - Suci Wulan Sari; Muh. Jazuli Asyrorroji; Sakinah Mardiyatillah (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2026)
This study looks at what drives GDP per capita growth in five developing countries—Indonesia, Malaysia, Bangladesh, Pakistan, and Turkey—between 2010 and 2024. Unlike most research that studies investment, trade openness, inflation, and financial development separately, this analysis examines how these factors work together, especially during times of global economic uncertainty. Using balanced panel data, the study measures the combined effects of investment, trade openness, inflation, and private credit on income growth. The analysis uses a Fixed Effects model with Panel-Corrected Standard Errors to handle issues like heteroskedasticity, autocorrelation, and cross-sectional dependence. The results show that increases in investment have a clear and positive effect on GDP per capita growth, highlighting the importance of building productive capacity. Trade openness does not have a significant link to income growth. On the other hand, higher inflation and more private credit are weakly linked to slower economic growth. Overall, the findings suggest that productive capital accumulation is the main driver of economic growth in these countries, rather than trade or financial development alone. The study suggests that policies should focus on encouraging investment, boosting industrial competitiveness, and making financial systems more efficient to support steady income growth.